Light-matter interaction in 2D transition metal dichalcogenide heterostructure : magneto photoluminescence, lasing, and photocurrent - Rasmita, Abdullah (Nanyang Technological University, 2020)
The two-dimensional (2D) transition metal dichalcogenide (TMD) features many properties that are desirable for applications in spintronics and valleytronics, as well as in excitonic devices, all of which aims for more energy-efficient devices. Moreover, even richer physical phenomena involving interlayer interaction can be observed when two TMD monolayers are stacked together creating, the 2D TMD heterostructure. This thesis presents the study of several aspects of the interaction between matter and light in the two-dimensional TMD heterostructure. First, the study regarding the MoSe2/WSe2 interlayer exciton dynamics under circularly polarized excitation and magnetic field influence is presented. We show that the interlayer exciton dynamic is affected by the dark WSe2 exciton. Moreover, we found that the interlayer exciton transition energy corresponding to maximum transition strength depends on the excitation polarization indicating a large optically induced pseudomagnetic field. Next, the study of the interaction between the MoS2/WSe2 interlayer exciton with light inside a cavity is presented. We show that the long interlayer exciton lifetime enables an excitonic laser with ultralow threshold power even with a low Q-factor cavity. Lastly, we show that the circular photogalvanic effect (CPGE) can be generated at the boundary between the 2D MoS2/WSe2 heterostructure and a metal electrode. The observed CPGE is due to the valley-dependent shift of the valence band induced by the combination of the built-in electric field and the optical selection rule of the valley as well as the different effective relaxation times between electron and hole in the 2D heterostructure. The findings presented in this thesis may be useful for realizing opto-valleytronics, opto-spintronics, as well as excitonic device applications which is based on 2D TMD heterostructure as a platform. We discuss several possible future research directions based on these findings.